Non-conventional MARCOM Strategy for Rural India - Kar, Sudhanshu Sekhar; Sahoo, Sarat Kumar (Indian Journal of Marketing, 2010)
The villages and small towns of India, which were once considered inconsequential from the marketing point of view, are now getting the attention of the marketers and rural markets are proving to be vital for the growth of most of the FMCG (Fast Moving Consumer Goods) companies. Rural India accounts for more than 30 - 60 per cent of the total sales of consumer goods like biscuits, toothpastes, shampoos, washing machines etc. Because of saturation in the urban markets, marketing strategy should shift its attention towards the rural markets, which are no longer seen as the dumping grounds of the consumer products popular in urban areas. Rural consumers have a distinct preference of their own. But due to perceptible changes seen in the improvement of infrastructure, rising level of income, explosion of media and wide coverage of TV, radio etc., the gap between the urban and rural divide is gradually narrowing. The rural consumer is more discrete, more cash-conscious and more utilitarian in outlook. The marketing communication i.e., MARCOM strategy for rural areas should be different from the urban areas because of inaccessibility of electricity and electronics media, thin population density and widely scattered villages, poor exposure, low disposable income and availability of counterfeit products.